Sex-age structure of pacific walrus Odobenus rosmarus divergens in the area of Cape Serdtse-Kamen’ (Chukchi Sea) in the summer-fall seasons of 2009-2014 - Maxim V. Chakilev; Anatoly A. Kochnev (Известия ТИНРО)
Sex and age structure of pacific walruses on the shore rookeries at Cape Serdtse-Kamen’ is considered on the data of observations in 2009-2014. In total, sex and age were determined for 13766 walruses. Adult females were the largest sex-age group - 42.95 %, adult males were 21.48 %, young animals of 3-5 years old - 12.73 %, yearlings (1-) - 12.31 %, calves in the age 1+ - 5.95 %, and calves 2+ - 4.58 %. The portion of parous females was 28.67 % of the total number of mature females that is a sign of low population replenishment. Mortality rate of walruses in the first three years of their life is estimated. Taking into account that up to 80 % of the population was concentrated in the area of observations, the data represent authentically the current status of the pacific walrus population.